The undivine Comedy : detheologizing Dante - Barolini, Teodolinda, 1951- (Princeton University Press, 1992)
The Undivine 'Comedy' is a vigorous, perceptive contribution to our reading of Dante's work and to our understanding of the problems he confronted as a narrative poet.